Pendekatan Eksistensial dalam Praktik Bimbingan dan Konseling - Uray Herlina; Ade Hidayat (Indonesian Journal of Educational Counseling, 2019)
EXISTENTIALISM APPROACH IN GUIDANCE AND COUNSELING PRACTICE. Existentialism could not be detached from Soren Kierkegaard’s idea, Nietzche’s, Karl Jaspers’s, then was developed by Martin Heidegger and Jean Paul Sarte who made existentialism become more outstanding. In psychology and Counseling, Existentialism approach get many influences from Kierkegaard opinion that opposes every efforts that view human being as an object, simultaneously opposes the subjective perception as only one human reality. Kierkegaard and many further existentialists, emphasize balancing between free-will and responsibility. Guidance and Counseling with existentialism approach appreciate democratic principle, emphasize dialog process, because freedom is one of choices. Based on this principle, every counselor has responsibility about value system which adopted by their counselee as long as it is not against with moral principle. Every counselor are demanded to behave ethically and rationally, and build value deeply and push their counselee to be responsible with their choice.